La transition identitaire de doctorant à professeur d’université : entre continuités et ruptures - Duchesne, Claire; Déri, Catherine; Le Callonnec, Lucie; Gagnon, Nathalie (Canadian Journal of Education/Revue canadienne de l’éducation, 2023)
This article examines the process of identity transition as experienced by new professors in tenure-track positions at four universities in eastern Canada. In this qualitative research, individual, semi-structured interviews were conducted with 24 participants. This article explores the tensions negotiated during the transitional process, particularly those associated with the construction of the new identity as a teacher. Finally, the discussion addresses the issues of continuity, rupture, and identity transition strategies.